2019
DOI: 10.3390/en12203854
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Crack Propagation in Cracked Concrete

Abstract: The intersection of cracks has an important role in the key technology of hydraulic fracturing for enhancing the recovery of tight hydrocarbon reservoirs. On the basis of digital image correlation technology, three-point bending tests of concrete beams with an edge crack and a central preset crack were conducted to investigate the propagation of cracks after intersection in concretes. Concrete beams with cracks of different positions, lengths, and approach angles were tested, and results were analyzed. In conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The research on concrete cracking is relatively extensive at home and abroad. It mainly focuses on the causes of cracks, crack control and numerical simulation, characteristics of cracks, and so on [10][11][12][13]. However, there are relatively few experimental studies on the carbonation law of concrete at the crack [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The research on concrete cracking is relatively extensive at home and abroad. It mainly focuses on the causes of cracks, crack control and numerical simulation, characteristics of cracks, and so on [10][11][12][13]. However, there are relatively few experimental studies on the carbonation law of concrete at the crack [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…RE a brittle material having low flexural strength and poor damage resistance when compared to contemporary building materials, requires improvement in the engineering properties. All types of soils have poor resistance to tensile stresses; hence, reinforcing them with discrete fibres has shown a very impressive improvement in the behaviour of soils (Li et al 2014;Hu et al 2021;Wang and Hu 2019;Jiang, Cai, and Liu 2010). While stabilizers like cement can help achieve durability and strength enhancement properties, fibres can provide ductility by improving their tensile and flexural strength.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of polypropylene fibres on the flexural properties of compressed earth blocks was studied and it was seen that when the fibre content exceeded 0.6%, the blocks exhibited deflection-hardening behaviour (Donkor, Obonyo, and Ferraro 2021). It is to be observed that during crack propagation, the crack driving forces always widen the cracks and the cohesive forces bridge the cracks (Wang and Hu 2019).…”
Section: Introductionmentioning
confidence: 99%